A Pilot Study on Covid and Autism: Prevalence, Clinical Presentation and Vaccine Side Effects - Natascia Brondino; Federico Bertoglio; Federico Forneris; Silvia Faravelli; Alessandro Borghesi; Stefano Damiani; Umberto Provenzani; Marta Nola; Miriam Olivola; Monica Caviglia; Pierluigi Politi; Laura Fusar-Poli; et al. (Brain Sciences, 2021)
Background: Several neurobiological mechanisms have been proposed to support the hypothesis of a higher COVID-19 risk in individuals with autism spectrum disorder (ASD). However, no real-world data are available on this population. Methods: We compared the period prevalence (March–May 2020) and symptom presentation of COVID-19 infections between a sample of individuals with severe ASD (n = 36) and the staff personnel (n = 35) of two specialized centers. Anti-SARS-Cov-2 antibody positivity was used as a proxy of infection. Additionally, we evaluated vaccine side effects in the same groups. Results: No significant difference was found between the prevalence of COVID-19 positivity between autistic participants and staff personnel. Levels of antibodies against the spike protein and the receptor binding domain were not significantly different between autistic and staff participants. The level of antibodies against the N-terminal domain were higher in autistic individuals. There was a significant difference between the prevalence of symptomatic COVID-19 in autistic participants (9.1%) compared to staff personnel (92.3%). The most frequent side effect among autistic participants was light fever. Conclusions: The present study provides preliminary data on COVID-19 transmission and presentation in ASD. Our data do not support the hypothesis of a higher susceptibility and severity of COVID-19 in people with ASD.